Clinical and hemodynamic outcomes of side-to-side anastomosis in superficial temporal artery-middle cerebral artery bypass for adult patients with moyamoya disease: a prospective cohort study - Zhiyong Shi; Zhongren Deng; Xinhua Chen; Lingyun Wu; Wei Li; Juan Wang; Yi Liu; Dong Zhang; Yi Wang; Chunhua Hang; Yongbo Yang (Frontiers in Neurology)
ObjectiveSuperficial temporal artery-middle cerebral artery (STA-MCA) bypass, characterized by side-to-side (S-S) anastomosis, has been beneficial in reducing the incidence of postoperative complications and recurrent stroke in patients with moyamoya disease (MMD). However, the safety and efficacy of this unconventional S-S procedure remain unclear. This research aimed to investigate the clinical and hemodynamic outcomes associated with the S-S technique.MethodsClinical and radiographic data were collected from 50 adult patients with MMD (50 hemispheres), including 23 cases treated with S-S anastomosis and 27 cases treated with end-to-side (E-S) STA-MCA bypass. The patients’ demographic information, clinical presentation, associated medical conditions, intraoperative hemodynamics, postoperative hemispheric perfusion status, and clinical course were obtained through a review of medical records, intraoperative microvascular Doppler ultrasonography (MDU), and postoperative CT perfusion (CTP) imaging.ResultsThere was no significant difference between the S-S and E-S groups in baseline characteristics, postoperative complications, bypass patency rate, neovascularization, and modified Rankin Scale (mRS) scores (p > 0.05). However, significant differences were noted in bypass time and anastomosis size between the E-S and S-S groups (p < 0.001). Intraoperative MDU analysis demonstrated that the mean velocity value (MVV) of the recipient artery entering the Sylvian fissure (RA.ES) and the MVV fold change in donor vessels were significantly higher in the S-S group compared to the E-S group (p < 0.05). Postoperative CTP analysis showed no difference in the volume of the infarct core, hypoperfusion, and penumbra between the groups (p > 0.05).ConclusionThe S-S technique demonstrated a different intraoperative self-flow regulation capacity compared to the traditional E-S technique, but it showed no superiority in postoperative hemispheric perfusion and clinical outcomes. The choice of bypass procedure should be individualized.